PENGARUH CITRA RUMAH SAKIT, PERSEPSI MASYARAKAT DAN WORD OF MOUTH TERHADAP KEPUTUSAN MEMILIH RUMAH SAKIT (STUDI DI RSUD HJ. ANNA LASMANAH BANJARNEGARA) - Maesaroh, Siti (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2022)
People's decision to choose a hospital as a place to fulfill health needs are often influenced by several factors, such as the image of the hospital, public perception and word of mouth. This study aims to find out whether there is an influence between the image of the hospital, public perception and word of mouth on the decision to choose a hospital either partially and simultaneously. This research is located at Hj. Anna Lasmanah Banjarnegara Hospital. This research is a quantitative study, collecting data with the dissemination of questionnaires. The population is outpatients and inpatients at Hj. Anna Lasmanah Banjarnegara Hospital. The sample in this study was as many as 100 people who conducted validity tests, reliability tests, normality tests, heteroskedasticity tests and multicollinearity tests. To test his hypothesis using the t test and the F test. The analysis technique used is multiple linear regression. The results showed that the image of the hospital, public perception and word of mouth influenced and significantly affected the decision to choose a hospital both partially and simultaneously. This is evidenced by the results of data processing using SPSS application version 25 whose calculation value shows the influence between variables. The coefficient of determination in this study was 0.752 (75.2%), meaning that the variable percentage of hospital image, public perception and word of mouth influenced the decision to choose a hospital by 75.2%.